1405 Is heavy vdt use a risk for visual field abnormalities among japanese workers?. (24th April 2018) - Tatemichi, M; Nakagawa, T; Honda, T; Owada, S; Endo, H; Hayashi, T; Nakano, T
Abstract : Introduction: The rapid global spread of information technology (IT), and most recently of new media (e.g., smartphones and tablets), has continually increased exposure to visual display terminals (VDT). This exposure is particularly marked among general workers. The health issues related to long-time VDT use are of great concern. Our previous large-scale, population-based study using frequency doubling technology perimetry (FDT) perimetry in the workplace indicated a possible association between a history of VDT use and glaucoma. Interestingly, we observed a significant interaction effect of myopia on the association between computer use and glaucoma; specifically, an increased risk of glaucomatous visual field abnormality (VFA) was observed only among frequent VDT users with myopia ( J Epidemiol Community Health, 2004;58(12):1021–7. etc.). However, those studies featured a cross-sectional design. We designed a retrospective cohort study to investigate the association between computer use and VFA using the FDT test. Methods: The study included 2377 workers (mean age 45.7±8.3 years) who initially exhibited no VFA during FDT testing. Subjects then underwent annual follow-up FDT testing for 7 years, and VFA were determined by using a FDT-test protocol (FDT-VFA). Subjects with FDT-VFA were examined by ophthalmologists. Baseline data about the mean duration of computer years during a 5 year period and refractive errors were obtained via self-administered questionnaire. Results: A Cox proportional hazard analysis demonstrated that heavy VDT users (>8 h/day) had a significantly increased risk of FDT-VFA (hazard ratio (HR)=2.85, 95% confidence interval (CI): 1.26–6.48) relative to light users (<4 h/day), and this association was strengthened among subjects with refractive errors (HR=4.48, 95% CI: 1.87 to 10.74). The VDT usage history also significantly correlated with FDT-VFA among subject with refractive errors (p<0.05), and 73.1% of subjects with FDT-VFA and refractive errors were diagnosed as glaucomatous. Conclusion: The incidence of FDT-VFA appears to increase among Japanese workers who are heavy VDT users, particularly if they have refractive errors. These results are consistent with findings of our previous studies. Further investigations of epidemiology and causality are warranted, because causal relationship between VDT use and glaucoma is unknown.